ANTIMICROBIAL ACTIVITY OF LACTOBACILLUS FERMENTUM, A VOLVO VAGINAL ISOLATE - Purkhayastha, Sumi Das; Bhattacharya, M. K.; Prasad, H. K.; Upadhyaya, H.; Pal, K.; Sharma, G. D. (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â Objective: Lactobacilli are the dominant bacteria of a healthy human vagina. They have antagonistic effect on potentially pathogenic microorganisms and vaginal pathogens. The aim of the present study was to find probiotic isolate from vaginal samples which can inhibit the growth of pathogenic microorganisms. Methods: A non-sporulating, catalase negative, Gram-positive bacteria was isolated from the vagina of a pregnant and identified women using 16s gene sequencing. The strain was identified to be Lactobacillus fermentum. The bacterium was grown in MRS broth for 24 hrs and the cell-free culture filtrate was used for antimicrobial assay. It has been found that minute quantity of culture filtrate (10 Î¼l) exhibit inhibition against Staphyloccous aureus (MTCC 3160) and Escherichia coli (MTCC 1060). Results: The cell free supernatant of bacterium identified as Lactobacillus fermentum, showed antimicrobial activity in minute doses (10Î¼l) by well diffusion method. Conclusion: It is suggested that this species of Lactobacilli could be considered for use in improving genital microfloral defense against Gram-positive and Gram-negative bacteria. Keywords: Lactobacillus, Human vagina, Probiotic microorganism, 16s gene sequencing.